Endovascular navigation in patients: vessel-based registration of electromagnetic tracking to preoperative images - Nypan, Erik; Tangen, Geir Arne; Brekken, Reidar; Aadahl, Petter; Manstad-Hulaas, Frode (Frontiers in Radiology, 2024)
Electromagnetic tracking of instruments combined with preoperative images can supplement fluoroscopy for guiding endovascular aortic repair (EVAR). The aim of this study was to evaluate the in-vivo accuracy of a vessel-based registration algorithm for matching electromagnetically tracked positions of an endovascular instrument to preoperative computed tomography angiography. Five patients undergoing elective EVAR were included, and a clinically available semi-automatic 3D-3D registration algorithm, based on similarity measures computed over the entire image, was used for reference. Accuracy was reported as target registration error (TRE) evaluated in manually selected anatomic landmarks on bony structures, placed close to the volume-of-interest. The median TRE was 8.2 mm (range: 7.1 mm to 16.1 mm) for the vessel-based registration algorithm, compared to 2.2 mm (range: 1.8 mm to 3.7 mm) for the reference algorithm. This illustrates that registration based on intraoperative electromagnetic tracking is feasible, but the accuracy must be improved before clinical use.